Heritage and Social Media : Understanding Heritage in a Participatory Culture - Giaccardi, Elisa (Taylor and Francis, 2012)
Heritage and Social Media explores how social media reframes our understanding and experience of heritage. Through the idea of 'participatory culture' the book begins to examine how social media can be brought to bear on the encounter with heritage and on the socially produced meanings and values that individuals and communities ascribe to it. To highlight the specific changes produced by social media, the book is structured around three major themes: Social Practice. New ways of understanding and experiencing heritage are emerging as a result of novel social practices of collection, representation, and communication enabled and promoted by social media. Public Formation. In the presence of widely available social technologies, peer-to-peer activities such as information and media sharing are rapidly gaining momentum, as they increasingly promote and legitimate a participatory culture in which individuals aggregate on the basis of common interests and affinities. Sense of Place. As computing becomes more pervasive and digital networks extend our surroundings, social media and technologies support new ways to engage with the people, interpretations and values that pertain to a specific territorial setting. Heritage and Social Media provides readers with a critical framework to understand how the participatory culture fostered by social media changes the way in which we experience and think of heritage. By introducing readers to how social media are theorized and used, particularly outside the institutional domain, the volume reveals through groundbreaking case studies the emerging heritage practices unique to social media. In doing so, the book unveils the new issues that are emerging from these practices and the new space for debate and critical argumentation that is required to illuminate what can be done in this burgeoning sector of heritage.